Agent-based Grid Automation in Distribution Grids: Experiences Under Real Field Conditions - Ludwig, Marcel; Korotkiewicz, Kamil; Dahlmann, Benedikt; Zdrallek, Markus (Proceedings of CIRED Workshop 2018 2018, 2018)
In this contribution, the experiences and results from the tests under real field conditions are described, which are concerned with grid automation systems in the research project Agent.HyGrid. Furthermore, the deployment of the grid automation system in a real-world distribution grid is discussed.